Characterization of Pro-aggressive Factors Influencing the Aggressive Behavior of Sex Offenders Serving their Sentences in Detention Facilities - Alexander V. Didenko; Oleg M. Pisarev; Ekaterina A. Mal'tseva (Психология и право, 2021)
In this research work we studied the structure and severity of pro-aggressive factors that influence aggressive manifestations in sex offenders serving their sentences in detention facilities. We carried out a comparative empirical study of two groups of male convicts serving their time for sexual (N=30) and mercenary crimes (N=30). The comparative analysis of aggressive behavior as well as the experimental and psychological research have been performed using the following: Buss A.H. & Durkee A. Hostility Inventory Questionnaire, Freiburg Personality Inventory, Ilyin Ye.P. and Kovalyov P.A. "Personality Aggression and Proneness to Conflict" methodology. It has been statistically proven that the aggression level in sex offenders prevails over that of mercenary criminals (p≤0.01) by the following parameters: physical, verbal and indirect aggression, irritability and sense of guilt. Prominence of pro-aggressive personality factors has been revealed in the convict sex offenders (irritability, quick temper at p≤0.01; neuroticism, depressiveness, reactive aggression, emotional instability at p≤0.05). Additionally, we discussed the influence of prison context on the aggression level.